Photodynamic Therapy Versus Glucose for the Treatment of Telangiectasia: A Randomised Controlled Study in a Rabbit Ear Model. (October 2019) - Buzzá, Hilde H.; Holmo Jr, Denizard; Stringasci, Mirian D.; Bertanha, Matheus; Leão, Patricia dos Santos; Fabro, Alexandre T.; Silva Jr, Nelson F.; Zangirolami, Amanda C.; Bagnato, Vanderlei S.; Yoshida, Winston B.
Abstract : Objectives: Telangiectasia is a common venous formation that mainly affects women and causes discomfort, including psychological distress. This study compared photodynamic therapy (PDT) with glucose for vessel sclerosis in a rabbit ear model. Methods: Thirty-six ears of 18 rabbits were randomly divided into four groups: Group 1: only injection of Photogem (4 mg/mL); Group 2: only light (635 nm, 100 mW/cm 2, 8 min, 48 J/cm 2 ); Group 3: glucose 75% injection; Group 4: PDT procedure with injection of Photogem and illumination immediately after. Injections were made into the central ear artery. After injection or sham procedures, manual compression of the marginal vein was maintained for 8 min in all ears. Follow up was immediately after the procedures, and one and six days later. The percentage of length reduction of spider veins, the target vessels, was analysed in digital photographs with Image J software. Ear thermographs were made with a thermocamera device and average temperatures were collected for analysis. Ear biopsies were obtained after six days. Endothelium average, inflammation, fibrosis, necrosis, skin burn, and vascular thrombosis were assessed using a specific score. Results: The mean vessel length reduction was 26% for Group 4, 2.4% for Group 3, .4% for Group 1, and 0 for Group 2, highlighting that in Group 4, the vessel lengths were significantly reduced compared with the other groups ( p  < .001). In the thermal analysis, in Group 3, the temperature was unchanged from the initial temperature and the central diameter vessel increased after six days, while, in Group 4, the temperature decreased and the vessels were not clearly detected, suggesting a reduction of the vessels and smaller infusion. Histology showed no difference among groups and one case of necrosis was found in Group 4. Conclusions: PDT was associated with significantly more target vessel sclerosis than glucose injection and controls.